Monetary policy and growth-at-risk: The role of institutional quality - Lorenz Emter; Afonso S. Moura; Ralph Setzer; Nico Zorell (European Central Bank (ECB), 2024)
This paper analyses how country-specific institutional quality shapes the impact of monetary policy on downside risks to GDP growth in the euro area. Using identified high-frequency shocks in a growth-at-risk framework, we show that monetary policy has a higher impact on downside risks in the short term than in the medium term. However, this result for the euro area average hides significant heterogeneity across countries. In economies with weak institutional quality, medium-term growth risks increase substantially following contractionary monetary policy shocks. In contrast, these risks remain relatively stable in countries with high institutional quality. This suggests that improvements in institutional quality could significantly enhance euro area countries' economic resilience and support the smooth transmission of monetary policy.
Keywords: C23; E52; F45; G28; O43; 330; Euro area; growth-at-risk; institutional quality; monetary policy transmission